A Systematic Critical Review: Flipped Learning and Its Impact on Self-Efficacy in Mathematics Education - Naufal Ishartono; Rizky Oktaviana Eko Putri; Kristof Fenyvesi; Manuel O. Malonisio (International Journal of Review in Mathematics Education, 2026)
Although the flipped learning model has been widely recognized to improve student engagement, its specific pedagogical effectiveness on self-efficacy in the context of abstraction-laden mathematics education has not been explored in depth. In addition, there has been no critical study that dissects the ambiguity of empirical findings related to operational challenges and cognitive burdens faced by students and educators in the field. Therefore, this critical review research aims to investigate the impact of the implementation of flipped learning on mathematical self-efficacy while identifying methodological and operational challenges in practice. The study adopted the PRISMA framework and the PICO search strategy to curate and critically evaluate 10 highly reputable empirical articles published in the 2020–2025 time frame from the Scopus, Web of Science, and ERIC databases. The results of the synthesis showed that flipped learning was significantly able to significantly improve math self-efficacy, mitigate anxiety, and serve as an equity intervention for low-performing students, especially when supported by self-regulated cognitive strategies (SRCS) and interactive media in the pre-grade phase. However, this success was severely limited by significant challenges, including students' difficulties in understanding abstract concepts independently, spikes in workload, as well as the scarcity of digital literacy and time constraints experienced by educators. Theoretically and practically, these findings provide an essential foundation for educators and policymakers to integrate pedagogical scaffolding and assistive technologies, such as AI-driven chatbots, to minimize students' cognitive barriers and design a more responsive and equitable future math learning ecosystem.